Polityka społeczna wobec ludzi starych w Polsce — uwarunkowania, rozwój i kierunki zmian - Wojtczak, Sylwia (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Social policy shapes people’s living conditions. In the era of dynamic demographic changes, especially the aging of the population observed in Poland and across the world, the activity of the state focused on improving the quality of life of the elderly is particularly important. Population aging is a demographic process of increasing the proportion of older people while reducing the proportion of children in the society of a given country. Elderly people will continue to be a part of society, mainly due to the progress of civilization, advances in modern medicine and the popularization of so-called healthy living. Social policy toward the elderly should not be limited to managing the social security system and social welfare. Effective use of human and social capital of the elderly will be a growing challenge for this policy, and for senior citizens — spending satisfactorily the last years of one’s life. However, for some senior citizens, old age means or will mean poverty and living on the margins of civil society. The Ministry of Family, Labor and Social Policy is responsible for the social policy of people in Poland, offering for example in the years 2014–2020 to senior citizens such programs as “Senior +”, the Government Program for Social Activity of the Elderly (ASOS) or “Care 75+.” Each of the above programs have appropriate criteria that must be met to be able to use them. Are older people eager to use them, or are the effects of these programs already visible? This study will attempt to answer the above questions. The main purpose of the article is to diagnose and analyze selected government programs targeted at older people. In addition, perspectives for changes in social policy toward older people in Poland will be determined.
Keywords: social policy; the elderly; Poland